Moments of impact : how to design strategic conversations that accelerate change - Ertel, Chris; Solomon, Lisa (Tantor Media, 2014)
Moments of Impact is a book on a mission: to eradicate time-sucking, energy-depleting workshops and meetings. In our fast-changing world, organizations have important challenges and opportunities to address-and no time to waste. Moments of Impact delivers the single most useful resource for managers and leaders who need better strategic conversation-now-to shape the future of their organizations. Moments of Impact is an essential guide for ambitious leaders who get assigned the hardest and most vexing strategic issues in their organizations, for entrepreneurs trying to manage board expectations, for social change agents pioneering new business models for community impact, for hopeful educators and healthcare practitioners trying to transform slow-to-change industries, and for enterprising students committed to tackling global challenges. Drawing on decades of combined experience as innovation strategists, Ertel and Solomon articulate the purpose, principles, and practices of well-designed strategic conversations. They weave together a lively and compelling mix of social science theories and research, interviews with more than one hundred thought leaders, organization leaders, and practitioners, as well as dozens of anecdotes and practical cases from diverse organizations. The book also includes a Starter Kit with diagnostic questions, best practices, and tips and suggestions to enable you to put the ideas to work immediately.